2021
DOI: 10.3389/fimmu.2021.709155
|View full text |Cite|
|
Sign up to set email alerts
|

Corticosteroids for Treating Sepsis in Adult Patients: A Systematic Review and Meta-Analysis

Abstract: ObjectiveCorticosteroids are a common option used in sepsis treatment. However, the efficacy and potential risk of corticosteroids in septic patients have not been well assessed. This review was performed to assess the efficacy and safety of corticosteroids in patients with sepsis.MethodsPubMed, Embase, and Cochrane library databases were searched from inception to March 2021. Randomized controlled trials (RCTs) that evaluated the effect of corticosteroids on patients with sepsis were included. The quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 78 publications
0
11
0
2
Order By: Relevance
“…Among these, cortisone, which has anti-inflammatory effects, was the most abundant differential metabolite. The latest Surviving Sepsis Campaign (SSC) guidelines recommend the use of corticosteroids in septic shock patients (moderate quality of evidence), and our latest meta-analysis also showed that corticosteroids improved intensive care unit and in-hospital survival (Evans et al, 2021;Liang et al, 2021), supporting the beneficial effects of corticosteroids in sepsis. Further, 6aminopenicillanic acid was the precursor of all semi-synthetic penicillin and could be introduced into different side chains to produce various antibiotics (Rolinson and Geddes, 2007).…”
Section: Discussionmentioning
confidence: 70%
“…Among these, cortisone, which has anti-inflammatory effects, was the most abundant differential metabolite. The latest Surviving Sepsis Campaign (SSC) guidelines recommend the use of corticosteroids in septic shock patients (moderate quality of evidence), and our latest meta-analysis also showed that corticosteroids improved intensive care unit and in-hospital survival (Evans et al, 2021;Liang et al, 2021), supporting the beneficial effects of corticosteroids in sepsis. Further, 6aminopenicillanic acid was the precursor of all semi-synthetic penicillin and could be introduced into different side chains to produce various antibiotics (Rolinson and Geddes, 2007).…”
Section: Discussionmentioning
confidence: 70%
“… 22 Recent systematic reviews and meta-analyses on the use of hydrocortisone in patients with sepsis and septic shock have provided disparate results. 5 , 23 , 24 …”
Section: Discussionmentioning
confidence: 99%
“…In the RECOVERY RCT, dexamethasone reduced 28-day mortality in patients receiving mechanical ventilation (MV; rate ratio = 0.64) and in those requiring oxygen treatment without MV (rate ratio = 0.82), but not in those who received no respiratory support (rate ratio = 1.19) [ 118 ]. These results were not surprising: steroid treatment had been tested previously (with mixed results) in patients with sepsis and ARDS [ 119 , 120 , 121 ]. In.…”
Section: Treatments Targeting the Host Response To Infectionmentioning
confidence: 99%